An experimental study on the effect of topicafly used atropine on tear production of dogs - Celal İzci; Sırrı Avki; Fahrettin Alkan (Eurasian Journal of Veterinary Sciences)
The study was undertaken to determine the effects of short and long-term local administration ol at-ropine.which is frequently used for treatment of various eye diseases and preanaesthetic medication,on tear production.Eight healty mongrel dogs were used in the study To observe the short-term effects of local atropine administration, the dogs have taken one drop of t% atropine sulphate solution on the right eye after obtaining the normal lacrimal secrete amount of right and left eyes by Schirmer I tear test and the tear values of each eyes were measured at 15,30,60,90,120,240,360 and 480 minutes intervals by same method e To confirme the long-term effects of atropine,the same animals have taken one drop of atropine solution or the right eye every morning and Schirmer I tear test values of each eyes were measured for seven days. After the completion of drug administration,measurements of each eyes were continued two times per day for seven days. The short-term use of atropine was resulted in a decrease of right eye tear production on an average of 34% after 90 minutes and approached to normal vaiues after 240 minutes meanwhile the left one had a decrease on an average of 22.7% after 60 minutes and reached to beginning values after 90 minutes.ln the long-term use of atropine, an increase of tear production was confirmed and found conspicuous statistically in the course of seven days after the completion of drug administration.